Results of Accelerated Local Cross-Linking in Keratoconus - H. Khraistin; G. A. Osipyan; S. I. Anisimov; A. K. Dzamikhova; M. Jourieh (Oftalʹmologiâ)
Objective of the study. To analyze the effectiveness of accelerated local corneal cross linking in the treatment of keratoconus (KC). Patients and methods. Thirty-four patients (42 eyes) were included in the study: 19 people (24 eyes) with stage II keratoconus, 15 people (18 eyes) with stage III Amsler keratoconus. All patients were examined using the following methods: visometry, refractokeratometry, keratotopography, optical coherence tomography of anterior segment, endothelial cell density calculation before and after surgical treatment in 6 months, 1, 2 and 3 years. Results. Significant increase of uncorrected (UDVA) and corrected (CDVA) distance visual acuity was registered 6 months after operation in KC of the II and III stages. In KC stage II, the NCOZ and EOC were greater, from 0.39 ± 0.14 to 0.61 ± 0.18 by 0.22 ± 0.04 (p < 0.05) and from 0.60 ± 0.15 to 0.77 ± 0.12 by 0.17 ± 0.03 (p < 0.05), respectively, in stage III. — from 0.12 ± 0.03 to 0.23 ± 0.07 by 0.12 ± 0.04 (p < 0.05) and from 0.45 ± 0.10 to 0.53 ± 0.12 by 0.10 ± 0.02 (p < 0.05), due to decreased refractive indices in the central 3.0 mm zone. Refractive indexes of the central corneal zone, UVA and CVA in all patients after one, two and three years, as well as data of minimal corneal thickness and endothelial cell density did not change statistically significantly during the entire observation period.